2019
DOI: 10.21475/ajcs.19.13.07.p1590
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the AquaCrop model in the climate risk analysis and yield prediction of cowpea (Vigna Unguiculatta L. Walp)

Abstract: The present work evaluated the Aquacrop model as a tool for climate risk analysis and yield prediction of cowpea, cultivated in a dystrophic yellow oxisol. The model was previously calibrated and validated for two harvests, in order to simulate the biomass and yield of cowpea, considering four applied water blades over its reproductive period. The good achieved results prove the model’s efficiency for this kind of simulation. After validation, the yield simulation of cowpea based on the meteorological data (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Bastos et al [21] observed a reduction of 60% in the productivity levels (grain yields) studying cowpea genotypes under water deficiency. Similar results were found by Hayatu and Mukhtar [5] and Nunes et al [10] that found reductions of 21.38%, 36.12% and 49.50% in treatments under water restriction. Souza et al [4] found significant reductions in the productivity of this cultivar when it was submitted to rainfed conditions, corresponding to a reduction of 41% under water deficiency of 26 mm, and 72% under a deficiency equal to 76 mm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bastos et al [21] observed a reduction of 60% in the productivity levels (grain yields) studying cowpea genotypes under water deficiency. Similar results were found by Hayatu and Mukhtar [5] and Nunes et al [10] that found reductions of 21.38%, 36.12% and 49.50% in treatments under water restriction. Souza et al [4] found significant reductions in the productivity of this cultivar when it was submitted to rainfed conditions, corresponding to a reduction of 41% under water deficiency of 26 mm, and 72% under a deficiency equal to 76 mm.…”
Section: Discussionsupporting
confidence: 91%
“…All sensors were connected to a CR10× datalogger (Campbell Scientific, Inc., Logan, UT, USA), configured for reading every ten seconds, recording total and average values every ten minutes. To quantify the deficiencies caused by treatments subjected to water deficit, the sequential water balance was carried out according to Carvalho et al; for more details, see in Nunes et al [10]. Accumulated soil water deficiency was obtained as a cumulative difference between daily ETc and daily actual evapotranspiration.…”
Section: Methodsmentioning
confidence: 99%